2008
DOI: 10.1017/s1744133108004611
|View full text |Cite
|
Sign up to set email alerts
|

Policy choice or economic fundamentals: what drives the public–private health expenditure balance in Canada?

Abstract: The public share of Canadian total health expenditure declined between 1975 and 2005 but categories such as physicians stayed constant while drugs, other institutions, and capital spending saw increases. Regressions find the key determinants of the public share to be: the relative price of health care, per capita income, federal transfers, proportion of population over age 65, provincial dummy variables, political parties, the onset of the Canada Health Act and the Canada Health and Social Transfer (CHST), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 54 publications
0
11
0
1
Order By: Relevance
“…3 At a more disaggregated level, spending on public health in the Canadian provinces appears to be driven by government ideology. The results by di Matteo (2009), for example, suggest that center-left parties are associated with smaller public shares for spending on health professionals and larger shares for total health spending. 4 Ideology-induced responses to globalization tended to depend on the level of unionization: when unionization was high and globalization was proceeding rapidly, leftwing governments have reduced public spending in the Canadian provinces (Pickup 2006).…”
Section: Partisan Politics In Canadian Provincesmentioning
confidence: 99%
“…3 At a more disaggregated level, spending on public health in the Canadian provinces appears to be driven by government ideology. The results by di Matteo (2009), for example, suggest that center-left parties are associated with smaller public shares for spending on health professionals and larger shares for total health spending. 4 Ideology-induced responses to globalization tended to depend on the level of unionization: when unionization was high and globalization was proceeding rapidly, leftwing governments have reduced public spending in the Canadian provinces (Pickup 2006).…”
Section: Partisan Politics In Canadian Provincesmentioning
confidence: 99%
“…Moreover, an increasing amount of empirical evidence suggests that income differentials affect access both to public and private sector services [32,33] and the private-public expenditure mix [34]. Several studies examine the interaction between income and waiting lists and show that patients with higher economic status are more likely to opt for the treatment in the private sector [35].…”
Section: Introductionmentioning
confidence: 99%
“…The question arises about the sign of the economic growth in developed, developing and underdeveloped countries. Some studies such as Hsieh and Lai (1994), Rasiah and Shari (2001), Rodden (2003), Loizidies and Vamvoukas (2005), Barro (2005), Moraga and Pierre (2008), Futagami et al (2008), Marrero (2008), Mourmouras and Peter (2009), Constantinos (2009), Hashimzade and Myles (2010), Park (2010), Dioikitopoulos and Kalyvitis (2010), Martin and Vanberg (2013), Palazuelos (2013) and Esen and Bayrak (2015) have found that government expenditures promote economic growth, while other studies, such as Barro (1990), Lipsmeyer (2002), Simonazzi (2003), Weller (2004), Noorudin and Simmons (2006), Garrett and Wheelcok (2006), Mattaeo (2009), Drmaechea and Marozumi (2013), Besley et al (2010), Faricy (2011), Ellis and Faricy (2011), Barro and Redlick (2011), Taylor et al (2012) and Rickard (2012) support the view that the expenditures hinder economic growth. Fan and Rao (2003) and Akitoby et al (2006); making their analysis for the 51 developing countries and found that there is long run positive co-integration relationship between the government expenditures and economic growth under the output channel; while the Wagner's law also hold.…”
Section: Literature Reviewmentioning
confidence: 99%